New Properties of Dual Continuous K-g-Frames in Hilbert Spaces - Abdeslam Touri; Hatim Labrigui; Mohamed Rossafi (International Journal of Mathematics and Mathematical Sciences, 2021)
The concept of frames in Hilbert spaces continues to play a very interesting role in many kinds of applications. In this paper, we study the notion of dual continuous K-g-frames in Hilbert spaces. Also, we establish some new properties.